OMBUDSMAN IN TURKEY: ITS CONTRIBUTIONS AND CRITICISM - Karasoy, H. Alpay (European Scientific Journal, ESJ, 2015)
Ombudsman institution is an independent, impartial, and a legal body which aims to protect the ruled ones against the trend of lawful authority, eliminate bad management practices, and act upon a complaint or ex officio. Ombudsman has authority in the investigation of incident, analysis, and in the making of announcement to the general public. With the legal arrangement made in Turkey, ombudsman institution has an Ankara-based special budget and legal entity connected to the Grand National Assembly of Turkey. The transition of the ombudsman institution into a constitutional institution has made significant contributions to both public administration and also to the citizens. This paper aims to study the various contributions and criticisms of the ombudsman institution in our country, Turkey.